2016
DOI: 10.1097/mib.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Center Experience of Vedolizumab Effectiveness in Pediatric Inflammatory Bowel Disease

Abstract: Our results suggest that vedolizumab is efficacious and safe in pediatric IBD patients, with UC patients experiencing earlier and higher rates of remission than CD patients. Anti-TNF-naive patients experienced higher remission rates than those with anti-TNF exposure. Controlled clinical trial data are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 13 publications
3
86
1
3
Order By: Relevance
“…Vedolizumab also benefits one-third of patients with IBD who failed to previous anti-TNF therapy in a phase III trial [17]. Vedolizumab is efficacious and safe in pediatric IBD patients too, with UC patients experiencing earlier and higher rates of remission than CD patients in a multicenter experience trial [18]. Mongersen, an oral SMAD7 antisense oligonucleotide, which targets SMAD7 to increase the activity of TGF β , induces significantly higher rates of remission and clinical response than placebo in patients with active CD in a phase II trial [19].…”
Section: Recent Advances In Biologics Treatment and Clinical Trialmentioning
confidence: 99%
“…Vedolizumab also benefits one-third of patients with IBD who failed to previous anti-TNF therapy in a phase III trial [17]. Vedolizumab is efficacious and safe in pediatric IBD patients too, with UC patients experiencing earlier and higher rates of remission than CD patients in a multicenter experience trial [18]. Mongersen, an oral SMAD7 antisense oligonucleotide, which targets SMAD7 to increase the activity of TGF β , induces significantly higher rates of remission and clinical response than placebo in patients with active CD in a phase II trial [19].…”
Section: Recent Advances In Biologics Treatment and Clinical Trialmentioning
confidence: 99%
“…High baseline abundance of Bifidobacterium , Clostridium colinum , Eubacterium rectale , uncultured Clostridiales and Vibri o, together with a lower abundance of Streptococcus mitis , predicted response to anti‐TNF therapy in one study (Table S4). Recently, a lower baseline dysbiosis index and higher abundance of Faecalibacterium prausnitzii were associated with subsequent clinical and endoscopic response, however these findings lacked statistical significance …”
Section: Resultsmentioning
confidence: 99%
“…Evidence supporting the faecal microbiota composition as a predictor of therapeutic response in IBD is accumulating. Both the relative abundance of several (most frequently butyrate‐producing) microbiota species and functional pathway analysis may accurately predict response to anti‐TNF, VDZ and UST treatment . This area warrants further research and microbiome data need to be incorporated into multi‐omics analyses.…”
Section: Discussionmentioning
confidence: 99%
“…176 The retrospective case reports of pediatric patients with IBD found that vedolizumab tended to be slower acting and have lower remission rates in patients with CD compared to those with ulcerative colitis. 177,178 Long-term, open-label follow-up data report low rates of infusion reactions, serious infections, and malignancy. 179,180 The consensus group did not make a recommendation for or against the use of vedolizumab in patients who had failed prior anti-TNF therapy.…”
Section: No Consensus Mmentioning
confidence: 99%